2022
DOI: 10.1021/acs.macromol.2c01268
|View full text |Cite
|
Sign up to set email alerts
|

Copolymers Prepared by Exchange Reactions Enhance the Properties of Miscible Polymer Blends

Abstract: Although many polymers are not miscible or chemically incompatible, some form miscible blends, which feature tunable properties relative to those of their constituent polymers. Here, we introduce an approach to enhance the mechanical properties of miscible blends of a thermoplastic polyurethane and a sustainable polyester, polycaprolactone (PCL), by introducing a copolymer of the two corresponding monomers. Rather than polymerizing the copolymers from new monomers, they were generated by a solvent-free, ester/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previously, we developed a 13 C NMR spectroscopy method to quantify the exchange between a thermoplastic polyester and TPU by integrating their distinct carbonyl resonances. 31 We applied this method to chemically distinct TPUs to evaluate the catalyst activity of pristine, activated, and self-heated Zr catalysts (Figure 2). Two TPUs were prepared for the crossover experiment: the first was synthesized from toluene-2,6-diisocyanate (TDI) and an aliphatic diol, and the second was synthesized from diphenyl diisocyanate (MDI) and an aromatic diol (Figure 2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we developed a 13 C NMR spectroscopy method to quantify the exchange between a thermoplastic polyester and TPU by integrating their distinct carbonyl resonances. 31 We applied this method to chemically distinct TPUs to evaluate the catalyst activity of pristine, activated, and self-heated Zr catalysts (Figure 2). Two TPUs were prepared for the crossover experiment: the first was synthesized from toluene-2,6-diisocyanate (TDI) and an aliphatic diol, and the second was synthesized from diphenyl diisocyanate (MDI) and an aromatic diol (Figure 2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Quantitative 13 C NMR spectroscopy was used to monitor carbamate exchange between thermoplastic urethanes (TPUs), and this experiment showed that the rate of carbamate exchange increases after Zr­(acac) 4 is heated in the presence of the polymers (Figure ). Previously, we developed a 13 C NMR spectroscopy method to quantify the exchange between a thermoplastic polyester and TPU by integrating their distinct carbonyl resonances . We applied this method to chemically distinct TPUs to evaluate the catalyst activity of pristine, activated, and self-heated Zr catalysts (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, the random exchange reaction between two different types of polymers (polyurethane and polyester) was achieved to synthesize a copolymer of polyurethane and PCL during the coextrusion of the two homopolymers at 200 °C by Dichtel's team. 24 Besides, the transesterification between poly(glycolic acid) and "nonpolymerizable" γ-butyrolactone (BL) was conducted by Hong and Chen 25 (Scheme 1, Route b). Based on the difference in transesterification ability between the polymer and monomer, they successfully incorporated BL into PGA to obtain copolymer poly(GA-co-BL).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Poly­(lactic acid- stat -salicylic acid) was successfully prepared through the intermolecular random transesterification of poly­(salicylic methyl glycolide) and PLA at elevated temperatures (Scheme , Route a). Moreover, the random exchange reaction between two different types of polymers (polyurethane and polyester) was achieved to synthesize a copolymer of polyurethane and PCL during the coextrusion of the two homopolymers at 200 °C by Dichtel’s team . Besides, the transesterification between poly­(glycolic acid) and “nonpolymerizable” γ-butyrolactone (BL) was conducted by Hong and Chen (Scheme , Route b).…”
Section: Introductionmentioning
confidence: 99%